2020
DOI: 10.1093/ehjci/ehaa946.2311
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of central aortic pressure and pulse pressure amplification changes in patients with aortic aneurysm: the role of aortic diameter and aortic aneurysm location level

Abstract: Background The presence of aortic aneurysm can alters pulse wave propagation and reflection, causing changes in central aortic pressure and pulse pressure amplification (PPA) between the aorta and the brachial artery that might be associated with unfavorable hemodynamic effects for the central arteries and the heart. However, the impact of the location of the aneurysm and increase of the aortic diameter on central blood pressure (CBP) is not fully understood. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…14). This result correlates with in-vivo measurements in patients with aortic aneurysms, where the radius increase has been associated with a lower central pulse pressure [3]. In addition, other numerical studies have found a decrease in the amplitude of the blood pressure and flow due to aneurysms [44].…”
Section: Discussion and Perspectivessupporting
confidence: 85%
See 1 more Smart Citation
“…14). This result correlates with in-vivo measurements in patients with aortic aneurysms, where the radius increase has been associated with a lower central pulse pressure [3]. In addition, other numerical studies have found a decrease in the amplitude of the blood pressure and flow due to aneurysms [44].…”
Section: Discussion and Perspectivessupporting
confidence: 85%
“…Abnormal geometry alterations caused by pathological conditions such as local expansions (aneurysms) and reductions (stenoses) of the radius, modify the pulse waveforms. For instance, in patients with aortic aneurysms, the increase in the radius has been associated with a lower central pulse pressure and a smaller PWV [3]. Waveform analysis in healthy and pathological conditions can be performed in the time or frequency domains [4][5][6].…”
Section: Introductionmentioning
confidence: 99%